PENGARUH INDEKS PEMBANGUNAN MANUSIA (IPM) DAN TINGKAT PENGANGGURAN TERBUKA TERHADAP TINGKAT KEMISKINAN INDONESIA TAHUN 2012-2022 - Mona Khairida; Lisda Aisyah; Ghina Rabbani (Al-Ujrah | Jurnal Ekonomi Syariah, 2023)
: The purpose of this study is to identify and analyze research related to the Human Development Index (IPM) and open unemployment to poverty in Indonesia in 2012-2022 for 10 years. The method used is quantitative with multiple linear regression analysis with the results of the HDI research (X1) having a significant effect on Poverty (Y) in Indonesia in 2012-2022. The Open Unemployment Rate (X2) has a significant effect on poverty (Y) in Indonesia in 2012-2022. Simultaneously the independent variables, namely HDI (X1) and the Open Unemployment Rate (X2) have a significant effect on poverty (Y) in Indonesia in 2012-2022.